Production of oxy-hydrogen with an alkaline electrolyzer, and its impacts on engine behaviors fuelled with diesel/waste fish biodiesel mixtures supported by graphene nanoparticles - El-Shafay, A. S.; Agbulut, Umit; Shanmugan, S.; Gad, M. S. (PERGAMON-ELSEVIER SCIENCE LTD, 2025)
Because of the high viscosity, low calorific value, atomization, and vaporization problems of biodiesel, addition of nano additives with oxyhydrogen is encouraged to improve engine combustion and emissions. Waste fish methyl ester was blended with diesel oil in 20 %, and then nano graphene was added to diesel-biodiesel mixtures at doses of 25, 50, and 100 mg/L. An alkaline electrolyzer was employed to generate oxyhydrogen gas at a rate of 0.5 L per minute through water electrolysis. At 3000 rpm rated speed and engine load range from 25 to 100 % with the interval of 25 % were investigated. Mixtures of graphene in methyl ester combinations have increased the thermal efficiency of biodiesel blend by 11 %, 13 %, and 15 %, respectively, when supplemented with HHO. The addition of 25, 50, and 100 ppm of graphene to the methyl ester was mixed along with oxyhydrogen, resulting in notable reductions of CO emissions by 18 %, 22 %, and 25 % for WF20. Significant decreases in HC emissions by 29 %, 32 %, and 38 %, accompanied by noticeable declines in smoke concentrations of 25 %, 28 %, and 33 % for WF20G25 + HHO, WF20G50 + HHO, and WF20G100 + HHO were shown. Moreover, NOx emissions experienced reductions of 20 %, 24 %, and 29 % when HHO was added to methyl ester blends containing 25, 50 %, and 100 ppm of graphene, respectively. Incorporating biodiesel from waste fish oil, enriched with 100 ppm graphene with HHO shows potential for lowering exhaust emissions, and enhancing engine performance and combustion characteristics, particularly for the commonly used biodiesel with poor fuel properties.
Keywords: Graphene nano additive; Oxy-hydrogen production; Waste fish biodiesel; Engine performance; Waste to energy; COMPRESSION IGNITION ENGINE; EMISSION CHARACTERISTICS; METHYL-ESTER; OIL BIODIESEL; HHO GAS; PERFORMANCE; COMBUSTION; OXIDE; ADDITIVES; Thermodynamics; Energy & Fuels